Performance-based clinical tests of balance and muscle strength used in young seniors: a systematic literature review - Bergquist, Ronny; Weber, Michaela; Schwenk, Michael (BMC geriatrics, 2019)
Many balance and strength tests exist that have been designed for older seniors, often aged ≥70 years. To guide strategies for preventing functional decline, valid and reliable tests are needed to detect early signs of functional decline in young seniors. Currently, little is known about which tests are being used in young seniors and their methodological quality. This two-step review aims to 1) identify commonly used tests of balance and strength, and 2) evaluate their measurement properties in young seniors.
Gesehen am 15.05.2019